Feasibility of Controlling Gas Concentration and Temperature Distributions in a Semiconductor Chamber with CT-TDLAS - Hayashi, Daisuke; Nakai, Junya; Minami, Masakazu; Kamimoto, Takahiro; Deguchi, Yoshihiro (Journal of Vibration Testing and System Dynamics, 2026)
The feasibility to control the gas concentration and temperature distributions in a semiconductor process chamber by measuring them was investigated. Gas concentration and temperature distributions for various flow rates were measured with the computed tomography-tunable diode laser absorption spectroscopy (CT-TDLAS). The infrared absorption spectra of multiple laser paths passing through the measured area were collected and the distributions of methane concentration and temperature in the chamber were reconstructed with the computed tomography (CT) calculations. The measured results indicated that the distributions can be independently controlled by measuring with the CT-TDLAS and adjusting the flow rates and the susceptor temperature.